A lab-scale experiment on low-temperature coal oxidation in context of underground coal fires. (August 2018) - Li, Jun; Fu, Pengbin; Zhu, Qiren; Mao, Yandong; Yang, Cheng
Highlights: A lab-scale experimental setup to simulate underground coal fires is established. Natural convection of air is the primary driving force for the chemical reactions. Temporal variation of surface thermal anomaly and CO/CO2 emissions are studied. Correlations between the coal temperature and other parameters are identified. Abstract: Underground coal fires (UCFs) cause remarkable loss of energy resources and significant environmental pollution. Understanding the fundamental characteristics of low-temperature oxidation of coal is related to the prevention and detection of UCFs. A lab-scale experimental setup is designed and built to study the coal spontaneous combustion under the natural convection of air into the coal layer. Alumina porous ceramic blocks with through-cuts are employed to simulate the overburden above the coal seam. Temporal variation of coal temperature, exhaust gases temperature and volumetric fractions of CO and CO2 are measured and analyzed. In addition, the thermal anomaly on the overburden surface is monitored, and its correlation with the underneath coal temperature is identified. It is found that air supply is the primary limiting factor that dictates the intensity of coal-oxygen reactions, and the ratio of CO2 /CO in the exhaust gases exhibits a strong dependence on the regime of coal-oxygen reactions.